A Review on Conventional and Modern Techniques to Develop Orodispersible Films - Verma, Dr. Surajpal (Asian Journal of Pharmaceutics (AJP), 2018)
Nowadays, solubility of active pharmaceutical ingredient (API) is one of the biggest challenges faced by the researchers during the development of pharmaceutical oral dosage form. Developing a new molecule is very expensive than formulating a dosage form of existing API. Orodispersible film (ODF) is one of the alternatives for the conventional dosage form as it dissolves and directly absorbed from the mouth. It is suitable for the delivery of poorly soluble drugs. It does not require water for the administration and gives quick absorption and high bioavailability. There are various techniques that can be used to improve the solubility of poorly soluble drugs in ODFs, namely, surfactants, superdisintegrants, and printing technology. Water-soluble polymers are used as the film former, but the different concentration and different combination of polymers and use of various additives like surfactant; superdisintegrants can show the significant effect on the solubility. It can be used for both local and systemic action. ODFs are gaining popularity and are widely accepted by the consumers, but it is still lacking in some areas due to the absence of pharmacopoeial specifications for disintegration, mechanical properties, etc.